Minerals from the Pohorje igneous massif - Zupančič, Nina (Geologija, 1994)
The mineralogical composition of Pohorje igneous rocks was determined by means of optical microscopy and X-ray powder diffraction. Quartz, plagioclases and K-feldspars are the major minerals in the granodiorite and its porphyritic varieties. Characteristic and accessory minerals are biotite, hornblende, apatite, orthite, epidote, zircon and opaque minerals. Muscovite, pyroxenes and garnets occur rarely. The major minerals in malchites are plagioclases and hornblende. Restitic crystals of plagioclases, apatite and zircon were present in magma from which the Pohorje igneous body solidified. Sulphides, apatite and zircon precipitated in the first stage of magma crystallisation. In the next stage orthite, epidote and sphene crystallized. Biotite crystals probably formed slightly before hornblende. The precipitation continued with plagioclases, quartz of first generation, more acid plagioclases, biotite and quartz of second generation. The crystallisation sequence ended with K-feldspar that replaced other minerals. The primary minerals are somewhere autometamorphosed to chlorite, epidote, calcite, sphene, sericite, kaolinite and limonite. In some areas in the NW part of Pohorje igneous body the alteration was hydrothermal.